2019
DOI: 10.1002/pa.2012
|View full text |Cite
|
Sign up to set email alerts
|

Interest groups on social media: Four forms of networked advocacy

Abstract: The affordances of social media both constrain and enable new forms of political advocacy. The present study identifies four forms of networked advocacy and analyses these with emphasis on constituencies, platforms, activities, and aims. Based on over 40 semistructured elite interviews with interest group leaders and heads of communication, it first finds that interviewees distinguish between social media platforms, tailoring content and genre, to target intended audiences. Second, it finds that social media a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 28 publications
1
34
0
1
Order By: Relevance
“…Our future systematic analyses may help to parse out some of these questions. Given the high number of posts that are currently getting coded as both inside AND outside lobbying, can we provide additional support for Figenschou and Fredheim's (2020) finding that social media can serve as a unique middle-stage form of lobbying, somewhere between inside and outside?…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…Our future systematic analyses may help to parse out some of these questions. Given the high number of posts that are currently getting coded as both inside AND outside lobbying, can we provide additional support for Figenschou and Fredheim's (2020) finding that social media can serve as a unique middle-stage form of lobbying, somewhere between inside and outside?…”
Section: Discussionmentioning
confidence: 88%
“…Obar, Zube and Lampe (2012) found that advocacy organizations favored Facebook for facilitating civic engagement and collective action. A study of Norwegian interest groups working in the health care sector found that organizations used Facebook for a wide range of activities, including educating the public and their membership, attracting members and funders, and mobilizing political action (Figenschou and Fredheim 2020). They used Twitter as a tool for direct communication with policymakers and other stakeholders.…”
Section: Social Media and Political Activitymentioning
confidence: 99%
See 2 more Smart Citations
“…With new communication technologies and platforms, ordinary people have gained opportunities to influence the form and content of news and public debates. Social media in particular represent an open, low-cost opportunity to provide information, mobilize supporters, raise funds, interact with multiple constituencies (Guo & Saxton, 2014;Lovejoy, Waters & Saxton, 2012;Vromen, 2017), and network with decision makers to achieve political impact (Figenschou & Fredheim, 2019). Extant studies of such personalized political communication and digital activism have largely focused on professional actors such as governments, interest groups or news professionals.…”
Section: Introductionmentioning
confidence: 99%